Urban heat island in Montes Claros – MG - Almeida, Maria Ivete Soares de; Silva, Lucas Augusto Pereira da; Leite, Marcos Esdras; Laurentino, Carla Milena de Moura; Marques, Samuel Carlos Santos; Leite, Manoel Reinaldo (Revista do Departamento de Geografia, 2020)
The objective of this work is to analyze the spatial distribution of the Heat Islands in the city of Montes Claros - MG. The choice of this area is justified by the population growth and the urban expansion that it has been going through in recent years. To carry out this work, it provided the use of remote sensing techniques for thermal modeling and wavelength indices. Orbital products from the Landsat 5 and 8 satellites (TM and OLI / TIRS sensors, respectively) were used for the dates: 08/28/1985 and 09/18/2016. The results showed that the spatial distribution of the Heat Islands is related to changes in the occupation and use of urban land, varying in spatiotemporal scale, intensifying in the central regions for positive anomalies, and in the edges presenting an increase in negative anomaly distributions. These are correlated with the increase of green areas in high standard condominiums. The elevated surface temperature temperature is proportionally related to NDBI and inversely to NDVI, considering the characteristics of the ground cover. This study is shown as an urban planning instrument, especially considering the aspects of land use and occupation for meteorological and climatic effects, considering that these elements are essential for human well-being.